The Role of the Teacher in Shapeing the Social Attitude of Students Through PKN Lessons in Class IV SDN 2 Telaga Biru Regency Gorontalo - Hakop Walangadi; Indrawati Butolo (Zien Journals, 2022)
The purpose of this study was to determine the teacher's role in shaping students' social attitudes through Civics subjects in grade IV at SDN 2 Telaga Biru, Gorontalo Regency. The research method used is descriptive qualitative. Data collection techniques used in the form of observation, interviews and documentation. Based on the results of research and discussion, that the role of teachers in shaping students' social attitudes through Civics subjects is good. To shape the behavior of students so that they have the habit of being social, good cooperation between the school and parents is needed because students spend a lot of time in the family environment. So efforts to implement student social attitudes are not only borne by the principal or class teacher, but all of this is the responsibility of the entire school and also parents. Therefore, it can be concluded that the teacher's role in shaping students' social attitudes needs to involve students' parents so that good cooperation is established in the formation of students' own social attitudes.
Keywords: Teacher's Role; Social Attitude; Civics Lessons